2015
DOI: 10.1021/acssuschemeng.5b00949
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Recycling of Carbon Fiber Reinforced Epoxy Resin Composites via Selective Cleavage of the Carbon–Nitrogen Bond

Abstract: An efficient strategy is developed for chemical recycling of cured epoxy resin (CEP) from its carbon fiber reinforced polymer composites (CFREP) using AlCl3/CH3COOH as the degradation system. Acetic acid swells the dense structures of CEP, facilitating the penetration of the aluminum ion catalyst into the polymer matrix. The weakly coordinating aluminum ions in CH3COOH solution selectively cleave the C–N bond while leaving the C–C, C–O (aryl alkyl ether) bonds intact. This process recovers valuable oligomers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 30 publications
3
87
0
Order By: Relevance
“…SI1 †). Fluidized bed [16][17][18] Solvolysis [9][10][11][12] Supercritical/ subcritical [13][14][15] Facility CFRP was purchased from Carbon Composites Company Limited (Hong Kong) with an epoxy resin content of 31.5%. Each layer of CF cloth is made by orthogonal weaving of longitudinal and transverse CFs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SI1 †). Fluidized bed [16][17][18] Solvolysis [9][10][11][12] Supercritical/ subcritical [13][14][15] Facility CFRP was purchased from Carbon Composites Company Limited (Hong Kong) with an epoxy resin content of 31.5%. Each layer of CF cloth is made by orthogonal weaving of longitudinal and transverse CFs.…”
Section: Methodsmentioning
confidence: 99%
“…5h, the surface of the CFs has deteriorated due to oxidation and exhibits pits and crack defects. 10,13,14 When the tensile test is conducted on a single fibre, this part becomes the critical section, and the stress concentration occurs near this section. Finally, fracture failure occurs in this section.…”
Section: Microstructural Characterization Of Rcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on sustainable and green chemistry aspects [26][27][28][29][30], chemical methods which are based on supercritical solvents in which an organic solvent or water with or without catalysts are the most promising methods. These methods can retain fibre strength up to >90% and generate a limited quantity of by-products and wastes [31][32][33][34][35]. Nevertheless, they are still considered high energy-consuming processes because of the fact that reaching the supercritical status of solvents requires high processing temperatures and extremely high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical recycling is however attracting increasing interest within the composites manufacturing community due to the possibility to obtain clean reclaimed fibers and, in some cases, valuable monomers from the epoxy matrix . Chemical recycling methods have been presented by several authors , and most recently the use of acetal links was reported as a way to develop recyclable epoxy composites . Kuang et al have described a reversible cross‐linked epoxy resin with efficient reprocessing properties prepared from a diamine Diels‐Alder adduct cross‐linker and a commercial epoxy oligomer .…”
Section: Introductionmentioning
confidence: 99%